Pengaruh Pembelajaran Berdiferensiasi Proses dengan Model Problem Based Learning (PBL) Terhadap Kemampuan Berpikir Kritis Siswa di SMP Negeri 1 Candung - Mailiyawati, Ghina; Lestari, Tuti; Arif, Khairil; Oktavia, Rani (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this article is to determine whether the effect of differentiated learning processes with the Problem Based Learning (PBL) model on students' critical thinking skills at SMP Negeri 1 Candung. The type of research used is quantitative using a quasi-experimental method with a Non-Equivalent Control Group Design. The differentiated learning process with the PBL model is applied to the experimental class while the control class uses conventional learning methods. The sampling technique is purposive sampling. The research instrument uses observation sheets, questionnaires and objective test questions. Data analysis uses normality tests, homogeneity tests and hypothesis tests. Based on the questionnaire, the implementation of differentiated learning processes with the Problem Based Learning model in the experimental class is 98.01%. The statistical analysis test in this study uses Microsoft Excel. Based on the results of the hypothesis test, the t count value is 2.240 and the t table is 2.001. So t count ≥ t table shows that there is a difference in the average between the experimental class and the control class. This means that there is a difference in the average critical thinking ability of students in the differentiated learning process with the PBL model at SMP Negeri 1 Candung. Meanwhile, students' responses to teachers in the learning process received a positive response from students of 94%.